2017
DOI: 10.5005/jp-journals-10015-1439
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ultrasonic and Manual Dynamic Agitation Techniques in Irrigant Penetration: An in vitro Study

Abstract: Aim:The aim is to compare the extent of irrigant penetration into root canals up to the working length and in simulated lateral canals after passive ultrasonic irrigation (PUI) and manual dynamic agitation (MDA). Materials and methods:Root canals of 36 single-rooted extracted teeth were shaped using rotary files. Irrigation was done with 5.25% sodium hypochlorite and 17% ethylenediaminetetraaceticacid. Teeth were decalcified in 5% nitric acid. Lateral canals were created by inserting 10 K-files and then, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In the included studies, thirteen studies reported the irrigant penetration up to the WL in terms of percentage ( 12 , 17 , 34 36 , 18 , 24 , 25 , 28 – 30 , 32 , 33 ). Seven studies ( 13 , 15 , 23 , 26 , 27 , 31 , 37 ) reported the irrigant penetration in terms of mean and standard deviation. Retrieving the raw data from the authors was attempted through e-mail communication, but only Sáinz-Pardo et al ( 27 ) responded with the raw data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the included studies, thirteen studies reported the irrigant penetration up to the WL in terms of percentage ( 12 , 17 , 34 36 , 18 , 24 , 25 , 28 – 30 , 32 , 33 ). Seven studies ( 13 , 15 , 23 , 26 , 27 , 31 , 37 ) reported the irrigant penetration in terms of mean and standard deviation. Retrieving the raw data from the authors was attempted through e-mail communication, but only Sáinz-Pardo et al ( 27 ) responded with the raw data.…”
Section: Resultsmentioning
confidence: 99%
“…Table 6 summarizes the results of all the individual studies. The results of six studies ( 13 , 15 , 23 , 26 , 31 , 37 ) were presented in terms of mean. Among these, five studies ( 13 , 15 , 23 , 31 , 37 ) presented the distance between the WL and the maximum irrigant penetration in terms of mean in straight and curved canals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation